140k views
4 votes
Solve the system of elimination
-3x+8y=-6
3x-2y=-12

User Agftrading
by
4.8k points

1 Answer

3 votes

Answer:

(- 6, - 3 )

Explanation:

Given the 2 equations

- 3x + 8y = - 6 → (1)

3x - 2y = - 12 → (2)

Adding the 2 equations will eliminate the x- term

0 + 6y = - 18

6y = - 18 ( divide both sides by 6 )

y = - 3

Substitute y = - 3 into either of the 2 equations and solve for x

Substituting into (2)

3x - 2(- 3) = - 12

3x + 6 = - 12 ( subtract 6 from both sides )

3x = - 18 ( divide both sides by 3 )

x = - 6

solution is (- 6, - 3 )

User MikeWu
by
5.1k points